(untitled) (Canadian Dermatology Today, 2021)
Coronavirus disease 2019 (COVID-19) is an acute systemic illness caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This novel coronavirus was first identified in Wuhan, China in late 2019 and has since had a major impact on global health after being declared a pandemic in the spring of 2020 by the World Health Organization. To date, there have been over 180 million confirmed infections and over 4 million deaths worldwide across multiple ‘waves’. COVID-19 has had a major impact on dermatology practice in Canada with a shift towards virtual care and a reluctance to prescribe some immunosuppressive medications. However, since those early days, there has been growing comfort with continuing such medications in most cases. The primary objective of this article is to review the impact of both COVID-19 and COVID-19 vaccination on patients with psoriasis who are taking oral agents and biologics (anti-tumour necrosis factor (TNF), anti-interleukin (IL)-17 and anti-interleukin (IL)-23 inhibitors).